PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA (PMRI) PADA POKOK BAHASAN TEOREMA PYTHAGORAS - Firilla Rahma Sari (Departemen Matematika, 2021)
This study aims to develop and produce student worksheets based on the PMRI approach on the subject of Pythagorean theorem valid and practical . The development model used in this study is the Plomp model developed by Tjeerd Plomp which consists of three phases, namely preliminary research, prototyping phase, and assessment phase. the preliminary research stage is carried out with the aim of knowing the design and characteristics of the student worksheets that will be developed. This phase is carried out in several stages, namely requirements analysis, curriculum analysis, concept analysis and student analysis. at the prototyping phase, the design of the Student Worksheet based on the PMRI approach was carried out according to the results of the preliminary research. Then a formative evaluation was carried out which consisted of self evaluation, expert review, one to one evaluation, and small group evaluation. The product was tested on VIII gradestudents of VIII SMPN 1 Gunung Talang . This study resulted in student worksheets based on the PMRI approach on the subject of the Pythagorean theorem with an validity value of 83.25% with a very valid category and an practicality value of 89.74% in a very practical category. Keywords– PMRI, Student Worksheets, Pythagorean Theorem